Evaluation of EFSA training courses on principles in chemical and biological risk assessment. Issue 5 (26th May 2022) - Escher, Sylvia E.; Bruer, Gustav; Creutzenberg, Otto; Schlemminger, Karin; Schulz, Florian; Ziemann, Christina; Rorije, Emiel; van Klaveren, Jacob; Posthuma, Leo; Bokkers, Bas; Slob, Wout; Hanberg, Annika; et al.
Abstract: This report evaluates the training courses delivered under the contract OC/EFSA/SCER/2017/01 ‐ Lot 1. Within the period of January 2018 to February 2022 a total of 21 training courses were provided, eight on‐site training courses in Parma at EFSA, six virtual training courses during the Covid‐19 pandemic and seven eLearning courses comprising various numbers of modules. The courses covered different aspects of chemical and biological risk assessment and related tools, namely i) harmonisation of risk assessment methodologies for human health and ecological risk assessment of combined exposure to multiple chemicals (mixture assessment), ii) risk assessment of the application of nanoscience and nanotechnologies in agro/food/feed (nanotoxicity); iii) science‐based criteria for identifying endocrine disruptors in the context of EU legislation on pesticides and biocides (endocrine disruption); iv) principles on genotoxicity on scientific assessment (genotoxicity) and v) computational toxicology approaches and tools (in silico). All tutors were experts in their field and had previously performed training courses on these topics. The target participants of the training courses were members of EFSA's Scientific Committee/Panels and their working groups as well as employees from national and international regulatory agencies associated with risk assessment of feed and food compounds. Members of the EFSA Networks as well as EFSA scientific staff also participated in the training courses. Courses were evaluated based on the feedback of participants and continuously improved also by integrating updated or new EFSA guidance documents.